Somsomido Restaurant - Zairan, Muhammad Rey; Juhili, Jailani; Kontuni, Merely; Albert, Suzanne; Jepinus, Jennifer (2013)
First of all, our company launched and pleasure introduced the new idea which wills generate profitability and sustainability in the market. The reasons that support the fact that our company will survive in the market because of we be the first Restaurant that serve famous traditional food in Sabah with unique landscape of Restaurant. All of our member company had been discussed and agree that our company name is Somsomido Traditional food. Why we choose this name because this name is a title of song that well known among people in Sabah. Therefore, when people hear and see about Somsomido they will remind any matter that related to Sabah whereby its people, cultural, place and Traditional food. We choose traditional food as our main product because almost Restaurant in Sabah not really exposed the Sabahan unique food to inside and outside people. Only certain that promoted this fantastic food but the amount not to large and can be calculated that amount. That's why we choose this courses of business simultaneously we strong believe that it will give 1001 advantages to us. Other than that, we have made a research about the market competition and we do not face tight competition in launching our new Restaurant that basis of traditional food. Our organization is different from other Restaurant because we serve the fresh 'Kampung' food that will give your feeling that food was cook by your mother and feel that you in your hometown. In order to give best customer service, we minimize the time to prepare the food to save our customers precious time. Other than that, our Restaurant landscape basis of cultural village for the purposes attract customer to come to our Restaurant. Our Restaurant concept in term of two option that food customer can take away or eat in our premises. In addition, customer can view mount Kinabalu while enjoy eat our food in our Restaurant. We choose Ranau as our business and office location because the existing large number of tourist in this place, why I said this place many tourist because it near with mount Kinabalu and have beautiful places around Ranau such as Memorial park and Poring.